Remote consequences of prematurity: violations of physical development and eating behavior of children and adolescents - Ju. S. Rafikova; M. A. Podporina; T. V. Saprina; E. V. Loshkova; E. V. Mikhalev; V. A. Stolyarova; T. A. Nagaeva; L. A. Agarkova; G. A. Мikheenko (Бюллетень сибирской медицины)
Aim. To characterize the physical development (PD) and eating behavior (EB) of children and adolescents born prematurely.Materials and methods. The study involved 123 people born in the period 1997-2008, 58 children born prematurely, age (12 ± 1.3) years, gestation period (33.07 ± 1.9) weeks (main group). The control group consisted of 65 full-term peers, age (12.7 ± 2.2) years, gestational age (39.5 ± 0.8) weeks. Participants were evaluated by PD (height, weight, body mass index (BMI), waist circumference (WC), throat circumference (TC)) under the WHO AnthroPlus program, and EB using the Dutch DEBQ questionnaire.Results. Growth and Z-score growth of boys and girls of the main group is lower than that of their fullterm peers, p = 0.04; 0.004 (p < 0.0001 for Z-score growth). Z-score BMI in boys and girls of the main group is higher than in full-term, p = 0.04; 0.01. WC/TC the girls of the main group is higher than in fullterm peers, p < 0.0001. In premature boys, the restrictive type is 13.3%, emotional and external – 50%, the combination of emotional and external – 33.3%. In the control restrictive – 5,7%, emotional – 28,6%, external – 32,3%, the combination of emotional and external – 10,8%, the combination of all three types – 5,7%. In the group of premature girls restrictive –7.1% against 36.7% in the control, (p = 0.007), emotsiogenic – 10.7% against 36.6% of the control (p = 0.02), external – 10.3% against 60% of the control (p = 0.003). In the control group the combination of external and emotiogenic – 16.7% (in the primary group is 0, p = 0.02). Preterm boys emotiogenic and external and their combination more often than girls (p = 0.001; 0.02; 0.001).Conclusion. Children and adolescents born prematurely are below full-term peers and have a high z-score of BMI. Boys realize violations of external and emotional types, and their combination.